LC478, a Novel Di-Substituted Adamantyl Derivative, Enhances the Oral Bioavailability of Docetaxel in Rats - Seung Yon Han; Qili Lu; Kyeong Lee; Young Hee Choi (MDPI AG, 2019)
P-glycoprotein (P-gp)-mediated efflux of docetaxel in the gastrointestinal tract mainly impedes its oral chemotherapy. Recently, LC478, a novel di-substituted adamantyl derivative, was identified as a non-cytotoxic P-gp inhibitor in vitro. Here, we assessed whether LC478 enhances the oral bioavailability of docetaxel in vitro and in vivo. LC478 inhibited P-gp mediated efflux of docetaxel in Caco-2 cells. In addition, 100 mg/kg of LC478 increased intestinal absorption of docetaxel, which led to an increase in area under plasma concentration-time curve (AUC) and absolute bioavailability of docetaxel in rats. According to U.S. FDA criteria (I, an inhibitor concentration in vivo tissue)/(IC50, inhibitory constant in vitro) >10 determines P-gp inhibition between in vitro and in vivo. The values 15.6–20.5, from (LC478 concentration in intestine, 9.37–12.3 μM)/(IC50 of LC478 on P-gp inhibition in Caco-2 cell, 0.601 μM) suggested that 100 mg/kg of LC478 sufficiently inhibited P-gp to enhance oral absorption of docetaxel. Moreover, LC478 inhibited P-gp mediated efflux of docetaxel in the ussing chamber studies using rat small intestines. Our study demonstrated that the feasibility of LC478 as an ideal enhancer of docetaxel bioavailability by P-gp inhibition in dose (concentration)-dependent manners.